Supervised physical exercise during pregnancy improves health perception. Randomised controlled trial - Mireia Peláez; Soraya Casla; María Perales; Yaiza Cordero; Rubén Barakat (FEADEF, 2013)
Aim: To investigate the influence of a moderate exercise program during pregnancy on the maternal health perception. Methods. A randomised controlled trial was performed. 101 primiparous women were allocated into the control group (CG, n=51) and the exercise group (EG, n=50), lost to follow-up 13, 11.4%. Women on the EC were asked to participate in a supervised exercise program during from 10-14 to 36 weeks of gestation (70-75 sessions, 55-60 min/session, three times per week). Women in the CG received usual care. All women were asked to fill in validated questionnaires about health perception and urinary incontinence before and after the intervention. Results. At the end of the intervention there were statistically significant differences between groups on health perception [very good: EG 35, 70% vs. CG 5, 9.8%; good: EG 15, 30% vs. CG 16, 31%; average EG 0, 0.0% vs. CG 26, 51%; poor EG 0, 0.0% vs. CG 3, 5.9%; very poor: EG 0, 0.0% vs. CG 1, 2% (p<.001)]. What is more, women in the EG showed less urinary incontinence [ICIQ-SF Score EG 0.30 (SD1.3) vs. CG 3.1 (SD4.1), p<.001]. Conclusions. A supervised physical exercise program during pregnancy which includes pelvic floor muscle training, improves health perception and it is effective on primary prevention of urinary incontinence.